Factors Predicting Locoregional Recurrence After Neoadjuvant Chemotherapy and Nipple-Sparing/Skin-Sparing Mastectomy With Immediate Breast Reconstruction - Wu, Zhen-Yu; Kim, Hee Jeong; Lee, Jong Won; Chung, Il Yong; Kim, Jisun; Lee, Sae Byul; Son, Byung-Ho; Eom, Jin Sup; Jeong, Jae Ho; Gong, Gyungyub; Kim, Hak Hee; Ahn, Sei-Hyun; et al. (Frontiers in Oncology, 2021)
Background Few data are available on the risk factors of locoregional recurrence (LRR) after neoadjuvant chemotherapy (NACT) and immediate breast reconstruction (IBR) in breast cancer. Herein, we evaluated the factors predicting LRR in a large series of patients who underwent either nipple- (NSM) or skin-sparing mastectomy (SSM) with IBR after NACT. Methods We retrospectively analyzed 609 breast cancer patients who underwent NACT and NSM/SSM with IBR between February 2010 and June 2017. Factors associated with an increased risk of LRR were analyzed by univariate (chi-square or Fisher’s exact test) and multivariate (Cox proportional hazard regression model) analyses. Results During a median follow-up of 63 months, LRR as the first event occurred in 73 patients, and the 5-year cumulative LRR rate was 10.8%. Multivariate analysis revealed post-NACT Ki67 ≥ 10% [hazard ratio (HR), 2.208; 95% confidence interval (CI), 1.295-3.765; P = 0.004], high tumor grade (HR, 1.738; 95% CI, 1.038-2.908; P = 0.035), and presence of lymphovascular invasion (LVI) (HR, 1.725; 95% CI, 1.039-2.864; P = 0.035) as independently associated with increased LRR risk. The 10-year LRR rate was 8.5% for patients with none of the three associated risk factors, 11.6% with one factor, 25.1% with two factors, and 33.7% with all three factors (P < 0.001). Conclusions Post-NACT Ki67 ≥ 10%, high tumor grade, and presence of LVI are independently associated with an increased risk of developing LRR after NACT and NSM/SSM with IBR. Future prospective trials are warranted to decrease the risk of LRR in patients with associated risk factors.